2019
DOI: 10.1093/inthealth/ihz074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antimicrobial susceptibility of bacterial isolates present in tap water of public toilets

Abstract: Background The present study was carried out to investigate the tap water quality of public toilets in Amritsar, Punjab, India. Methods Water samples from the taps of the public toilets were collected in sterile containers and physicochemical and bacteriological analysis was performed using standard methods. Also, genotypic and phenotypic characterization of the bacterial isolates was performed using different biochemical tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…It is a gram-negative, motile rod typically positive for oxidase, and they have non-fluorescent pigment-producing colonies for most but not all strains [16,17]. It belongs to the family Pseudomonadaceae as part of the P. aeruginosa group (P. aeruginosa, P. alcaligenes, and P. otitidis) [18,19]. The closest pseudomonal spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a gram-negative, motile rod typically positive for oxidase, and they have non-fluorescent pigment-producing colonies for most but not all strains [16,17]. It belongs to the family Pseudomonadaceae as part of the P. aeruginosa group (P. aeruginosa, P. alcaligenes, and P. otitidis) [18,19]. The closest pseudomonal spp.…”
Section: Discussionmentioning
confidence: 99%
“…P. otitidis was isolated from many environmental sources, such as soil, plants [17], food sources [24], different water bodies, sewage [25], and public toilets [18]. A recent article reported the presence of P. otitidis in the sewage water of Taif city in Saudi Arabia [26].…”
Section: Discussionmentioning
confidence: 99%
“…The strain RR014 was identified to the genus level by observing colony morphology and performing various biochemical tests such as indole test, Voges-Proskauer test, methyl red test, Simmons citrate agar test, triple sugar iron, motility, oxidation/fermentation, enzyme production (oxidase, catalase and urease), and carbohydrate fermentation (glucose, fructose, sucrose, mannitol, lactose). For 16S rRNA gene analysis, DNA of the strain RR014 was isolated from the overnight grown culture in LB medium as previously described by Kaur et al (2019). The 16S rRNA gene of the bacterial isolate was amplified in a reaction mixture (20 µl) using primers: 27F…”
Section: Isolation and Identification Of Bacillus Marisflavi Strain Rr014mentioning
confidence: 99%
“…A recent study reported that, 25 bacterial isolates were identified by 16S rRNA sequences analysis collected from public tap water in India, from the 25 isolates, 5 were of Bacillus (B. pumilus, B. flexus, B. megaterium, B. marisflavi and B. oceanosediminis). 23 In a recent study, Fancello et al reported that 72 isolates were purified from olive samples collected in Italy and according to the 16S rDNA sequencing analysis, the bacterial isolates primarily fitting to Bacillus spp., Brevibacillus spp., Micrococcus spp., Pantoea spp., Kocuria spp., Staphylococcus spp., Lysinibacillus spp. and Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that, 25 bacterial isolates were identified by 16S rRNA sequences analysis collected from public tap water in India, from the 25 isolates, 5 were of Bacillus ( B. pumilus, B. flexus, B. megaterium, B. marisflavi and B. oceanosediminis ). 23 …”
Section: Introductionmentioning
confidence: 99%